2021
DOI: 10.18805/ijar.bf-1425
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Naringenin on Cadmium-induced Toxicity in Rat Liver

Abstract: Background: Cadmium (Cd) is a widespread environmental toxic heavy metal. Naringin (Nar) is reported to have a protective effect on Cd-induced liver injury. This study aimed to explore the hepatic injury induced by Cd and the protective effects of Nar on Cd-induced oxidative stress and apoptosis in rat liver. Methods: In accordance with groups, male SD rats were injected intraperitoneally with Cd and orally with Nar every day. The treatment period was 3 weeks. Body weight, the morphological changes in liver, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In this study, it was also noteworthy that mercury chloride‐induced apoptotic increase decreased with naringenin administration (Table 6, Figures 3 and 4). Wang et al 62 demonstrated the ameliorative effects on hepatic structural damage and cell apoptosis of naringenin used against cadmium‐induced liver toxicity. It was reported that naringin, the glycan of naringenin, had a decreasing effect on increased KIM‐1, Caspase‐3, TGF‐β, and TNF‐α levels in liver and kidney, decreased apoptosis and thus ameliorated renal and hepatic damage in arsenic‐treated rats 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was also noteworthy that mercury chloride‐induced apoptotic increase decreased with naringenin administration (Table 6, Figures 3 and 4). Wang et al 62 demonstrated the ameliorative effects on hepatic structural damage and cell apoptosis of naringenin used against cadmium‐induced liver toxicity. It was reported that naringin, the glycan of naringenin, had a decreasing effect on increased KIM‐1, Caspase‐3, TGF‐β, and TNF‐α levels in liver and kidney, decreased apoptosis and thus ameliorated renal and hepatic damage in arsenic‐treated rats 63 .…”
Section: Discussionmentioning
confidence: 99%